Asymmetric Warming/Cooling Response to CO2 Increase/Decrease Mainly Due To Non‐Logarithmic Forcing, Not Feedbacks. Issue 5 (8th March 2022) - Mitevski, Ivan; Polvani, Lorenzo M.; Orbe, Clara
Abstract: We explore the CO2 dependence of effective climate sensitivity ( S G ) with symmetric abrupt and transient CO2 forcing, spanning the range 1/8×, 1/4×, 1/2×, 2×, 4×, and 8×CO2, using two state‐of‐the‐art fully coupled atmosphere‐ocean‐sea‐ice‐land models. In both models, under abrupt CO2 forcing, we find an asymmetric response in surface temperature and S G . The surface global warming at 8×CO2 is more than one third larger than the corresponding cooling at 1/8×CO2, and S G is CO2 dependent, increasing non‐monotonically from 1/8×CO2 to 8×CO2 . We find similar CO2 dependence in the transient runs, forced with −1%yr −1 CO2 and +1%yr −1 CO2 up to 1/8×CO2 and 8×CO2, respectively. The non‐logarithmic radiative forcing—not the changing feedbacks—primarily explains the dependence of S G on CO2, particularly at low CO2 levels. The changing feedbacks, however, explain S G 's non‐monotonic behavior. Plain Language Summary: Equilibrium climate sensitivity is the global mean warming after doubling CO2 concentrations from those of the year 1850. Since CO2 levels will likely surpass a doubling, it is crucial to know whether the amount of warming per CO2 doubling (which we refer to as the effective climate sensitivity, S G ) is constant with each CO2 doubling or whether it changes. Necessary conditions for constant S G are (a) the radiative forcing introduced to the climate system from each CO2 doubling is constant and (b) the net radiative feedback does not change with CO2 levels. Current literature shows that S G will increase in a warmer world because the radiative feedback will change. We here investigate S G in both warmer and colder worlds, and confirm that S G increases at higher CO2 concentrations. However, we show that changes in the radiative forcing with each CO2 doubling are mainly responsible for S G increase with CO2, not feedback changes. Key Points: The global surface temperature responds asymmetrically to increased and decreased CO2 levels, in both abrupt and transient cases Effective climate sensitivity is higher with warming (2×, 4×, 8×CO2 ) than with cooling (1/2×, 1/4×, 1/8×CO2 ), in two different coupled models The non‐logarithmic nature of the CO2 forcing is primarily responsible for the asymmetry, not the radiative feedbacks